Team regulatory strategies and performance in elite handball - Debanne, T.; Volossovitch, A. (Research Quarterly for Exercise and Sport, 2023)
Purposes: The purposes of this research were: 1) in a preliminary study, to identify regulatory strategies used by players and coaches according to situation reward structure (Gains vs. Losses); and 2) in the main study, to analyze the effect of the interaction between situation reward structure (Gains vs. Losses) and regulatory strategy (Prevention vs. Promotion) on team performance (scoring a goal) in real-world settings. Methods and Results: In the preliminary study, 25 adult male handball players and 19 coaches playing and coaching at national level in the French championships completed a version of the Regulatory Focus Strategies Scales after reading four handball game scenarios (two gain-oriented and two loss-avoidance oriented). Two-way ANOVA with repeated measures revealed that when the reward structure was gain-oriented, participants had higher scores in promotion regulatory strategy than in prevention regulatory strategy, and conversely. For the main study, a sample of 199 game phases was selected from 84 games played in the Lidl Star League (2017-2018 season). Mixed method analysis revealed a significant team regulatory fit effect, that is an interaction effect between reward structure and regulatory focus strategy on team performance. When there was a fit, both in loss-avoidance oriented and gain-oriented reward structure, performance was higher (OR = 1.64 and OR = 0.86, respectively) than when there was a mismatch (OR = 0.59 and OR = 0.27). Conclusion: These results confirm the applicability of the Regulatory Fit Theory in a real-world setting with professional players, and extend grounded social cognition research regulatory fit literature to team level.